Pedretti's occupational theraphy : practice skills for physical dysfunction - Pedretti, Lorraine Williams , 1936-; Pendleton, Heidi McHugh; Schultz-Krohn, Winifred (Mosby/Elsevier, 2013)
"Using a comprehensive, case-based learning approach, Pedretti's Occupational Therapy: Practice Skills for Physical Dysfunction, 7th Edition provides a thorough introduction to occupational therapy practice and prepares you to work with adults who have physical disabilities. 48 chapters cover everything from OT history, theory, process, and practice to evaluation, intervention, performance skills, and client factors. Significant updates have been made to this edition, including a new full-color design and new content on polytrauma and advances in prosthetics and assistive technologies. This leading text also offers a wide range of helpful features, such as threaded case studies, OT practice notes, and ethical considerations that help you apply content to a clinical setting."-- Publisher's website